Innovative Personality as a Social Type in the Transition to an Innovative Way of Development - Petrovskaya, Yuliya Aleksandrovna (International Journal of Psychosocial Rehabilitation, 2020)
Modern society of innovative technologies makes new demands on personal qualities and competencies that characterize personality as innovative. Traditional sociological approaches to the structure and typology of personality do not correspond to the objectively developed social reality and the level of achievements of modern cognitive sciences. The aim of the research is to determine the key characteristics of innovative personality as a social type in the society of innovative technologies and the conditions of its formation in the context of Russian civilization. The used research methods: theoretical analysis, secondary analysis of empirical descriptions, survey methods allowed to achieve this goal.